Keloids and Hypertrophic Scars: Update and Future Directions - Chenyu Huang, MD, PhD; George F. Murphy, MD, PhD; Satoshi Akaishi, MD, PhD; Rei Ogawa, MD, PhD, FACS (Plastic and Reconstructive Surgery, Global Open, 2013)
Summary: The development of cutaneous pathological scars, namely, hypertrophic scars (HSs) and keloids, involves complex pathways, and the exact mechanisms by which they are initiated, evolved, and regulated remain to be fully elucidated. The generally held concepts that keloids and HSs represent “aberrant wound healing” or that they are “characterized by hyalinized collagen bundles” have done little to promote their accurate clinicopathological classification or to stimulate research into the specific causes of these scars and effective preventative therapies. To overcome this barrier, we review here the most recent findings regarding the pathology and pathogenesis of keloids and HSs. The aberrations of HSs and keloids in terms of the inflammation, proliferation, and remodeling phases of the wound healing process are described. In particular, the significant roles that the extracellular matrix and the epidermal and dermal layers of skin play in scar pathogenesis are examined. Finally, the current hypotheses of pathological scar etiology that should be tested by basic and clinical investigators are detailed. Therapies that have been found to be effective are described, including several that evolved directly from the aforementioned etiology hypotheses. A better understanding of pathological scar etiology and manifestations will improve the clinical and histopathological classification and treatment of these important lesions.